Socialization, Learning Creativity by Coloring Canvas Bags at SD Nahdlatul Wathan Gabus Bekasi, Srimukti Village through the Real Work Lecture (KKN) program at Bhayangkara University, Jakarta Raya - Nanda Hanifah Putri (Jurnal Abdimas Ekonomi dan Bisnis, 2023)
Community empowerment is essentially bringing out the potential that already exists in peopleor groups by offering support and increasing awareness of this potential with the aim ofempowering people or groups to achieve their goals or produce effective societal changes thatcan change and improve socio-economic welfare. -in their environment. Community ServiceLecture (KKN) activities are educational in the sense of providing learning opportunities tostudents outside the classroom. In Srimukti Village, KKN SEJATI 2023 will be implementedthrough service modalities such as outreach, learning, and creativity. The results show a goodresponse from the community and children from the active involvement of SD NahdlatulWathan Srimukti. Keywords: Community Empowerment, Socio-Economic Welfare, KKN (Community ServiceLecture)